2016
DOI: 10.1016/j.canlet.2016.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Combined targeting of TGF-β, EGFR and HER2 suppresses lymphangiogenesis and metastasis in a pancreatic cancer model

Abstract: Pancreatic ductal adenocarcinomas (PDAC) are aggressive with frequent lymphatic spread. By analysis of data from The Cancer Genome Atlas, we determined that ∼35% of PDACs have a pro-angiogenic gene signature. We now show that the same PDACs exhibit increased expression of lymphangiogenic genes and lymphatic endothelial cell (LEC) markers, and that LEC abundance in human PDACs correlates with endothelial cell microvessel density. Lymphangiogenic genes and LECs are also elevated in murine PDACs arising in the KR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…Numerous studies have shown that EGFR is implicated in the oncogenesis and pathogenesis of PC. Small‐molecule EGFR inhibitors such as Gefitinib and Erlotinib are currently employed as targeted therapies for PC . However, resistance to this class of agents limits their efficacy in the clinic .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that EGFR is implicated in the oncogenesis and pathogenesis of PC. Small‐molecule EGFR inhibitors such as Gefitinib and Erlotinib are currently employed as targeted therapies for PC . However, resistance to this class of agents limits their efficacy in the clinic .…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of EGFR stimulates cascade of downstream signaling pathways, including the Ras/Raf/MEK/ERK, PI3K‐AKT, and the JAK/STAT3 signaling pathways, leading to tumor development and metastasis . Accordingly, EGFR signaling has become a popular molecular targeted therapy in cancer, including PC . EGFR inhibitors, according to their site of action, can be divided into two categories: one is the small‐molecule tyrosine kinase inhibitors (EGFR‐TKIs), including the currently used Erlotinib, Gefitinib and Afatinib; the other is the extracellular EGFR monoclonal antibodies that specifically bind EGFR, such as Cetuximab, Panitumumab, etc .…”
Section: Introductionmentioning
confidence: 99%
“…The EGFR signaling pathway can promote the occurrence and progression of a variety of neoplastic diseases through interactions with P53, IL-8, IL-6, and Transforming Growth Factor-Beta (TGF-β) signaling pathways, such as pancreatic, breast, and epithelial cancer. [21][22][23][24] IL-6, an important signal stimulating factor in lung cancer immunization, is closely related to the occurrence and poor prognosis of lung cancer. 25 In the current study, we found that the expression of IL-6 and GP130 was significantly high (Table 1) and was associated with poor prognosis in NSCLC ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of A disintegrin and metalloprotease 17 in LECs and treatment with an EGFR inhibitor resulted in both decreased motility and sprouting . Finally, dual inhibition of transforming growth factor beta and EGFR/HER2 using lapatinib suppresses the growth and metastasis of pancreatic ductal adenocarcinoma, which expresses many lymphangiogenic factors . Although there are promising results on the interaction between EGFR signaling and lymphangiogenesis, the detailed mechanisms have yet to be elucidated, and thus far, there have been no clinical trials specifically studying the pro‐/antilymphangiogenic effects of EGFR inhibitors on lymphangiogenesis‐related disorders or cancer metastasis.…”
Section: Lymphangiogenesis Mechanisms: Major Target Sitesmentioning
confidence: 99%